(untitled) (Third Sector Social Economic Review, 2012)
Agricultural and rural finance is a complex sector which intertwines with all acpects of economic and social development. Credit use is one of the most common area for the government to intervene in the market. The role of government in mitigating the poverty and developing the agriculture has been anticipated as a sufficient condition in providing credit with subsidized interest rate, however, whether or not the subsidized credit contributed to agricultural and rural development has not discussed. Therefore, credit use becomes an instruments causing only temporary recovery. The role of the Turkish Agricultural Credit Cooperatives (TKK) is also discussed in the study. Government gives a role to TKK in developing the rural areas. TKK is among the institutional credit organizations which provides credit to the rural areas. TKK aims at providing short and medium term credit for its members.